Simulation and Experimental Study of The Sensor Emitting Frequency for Ultrasonic Tomography System in a Conducting Pipe - Goh, Chiew Loon; Ruzairi, Abdul Rahim; Hafiz Fazalul, Rahiman; Tee, Zhen Cong; Yasmin, Abdul Wahab (Elsevier Ltd, 2017)
Ultrasonic tomography techniques provide flow visualization capability, non-invasively and non-intrusively, to enhance the understanding of complex flow processes. There is limited ultrasonic research in tomography imaging systems in the tomogram analysis of fluid flow in a conducting pipe because of a high acoustic impedance mismatch, which means that very little ultrasonic energy can be transmitted through the interface. The majority of industrial pipelines are constructed from metallic composites. Therefore, the development and improvement of ultrasonic measurement methods to accommodate a stainless steel pipe are proposed in this paper. Experimental and simulation distribution studies of the ultrasonic emitting frequency in acrylic versus stainless steel pipes were studied, measured and analyzed. During the simulation, ultrasonic transducers were placed on the surface of the investigated pipe to inspect the ultrasonic sensing field. The distribution of the sound wave acoustic pressure was simulated based on the physical dimensions and parameters of the actual experimental hardware set-up. We developed ultrasonic acoustic models using the finite element method with COMSOL software, and experiments were carried out to validate the simulation results. Finally, by performing the static phantoms tests, a feasibility study of ultrasonic tomography system was presented to investigate the void fraction of liquid column inside a stainless steel pipe.